Prevalence of Multidrug-resistant Escherichia coli in the Swine Production Chain: Implications for Food Safety in Brazilian Slaughterhouses - Pereira, Natalia; Silva, Leandro Augusto Mariano; Rodrigues, Romário Alves; Menezes, Mareliza Possa de; Moretto, Luis Felippe Agrião; Almeida, Camila Chioda de; Rossi, Gabriel Augusto Marques; Ávila, Fernando Antônio de; Cardozo, Marita Vedovelli (Food Science and Technology, 2025)
Multidrug resistance is a significant threat to global public health. This study aimed to detect and characterize antimicrobial-resistant microorganisms in swine feces and carcasses obtained from slaughterhouses. A total of 214 samples were collected, comprising 111 swine feces and 103 from carcasses, across two different slaughterhouses. Polymerase chain reaction was used to detect antimicrobial resistance genes, identifying 22 resistant isolates that were subsequently confirmed to be Escherichia coli. Pulsed-field gel electrophoresis was performed on these 22 isolates to investigate their genetic similarity. The Kirby–Bauer disk diffusion method characterized phenotypic resistance to different antimicrobials. The blaCTX-M-1 gene was detected in all 22 E. coli isolates. Additionally, 90.9% of the strains were considered multidrug-resistant, exhibiting resistance to at least three different antimicrobial classes. The isolates exhibited high genetic diversity. The presence of these multidrug-resistant bacteria in swine and animal-derived foods emphasizes the importance of sanitation measures during production to protect public health.